Regulation of Connexins Expression Levels by MicroRNAs, an Update - Calderón, Juan F.; Retamal, Mauricio A. (Frontiers in Physiology, 2016)
Control of cell-cell coordination and communication is regulated by several factors, including paracrine and autocrine release of biomolecules, and direct exchange of soluble factors between cells through gap junction channels. Additionally, hemichannels also participate in cell-cell coordination through the release of signaling molecules, such as ATP and glutamate. A family of transmembrane proteins named connexins forms both gap junction channels and hemichannels. Because of their importance in cell and tissue coordination, connexins are controlled both by post-translational and post-transcriptional modifications. In recent years, non-coding RNAs have garnered research interest due to their ability to exert post-transcriptional regulation of gene expression. One of the most recent, well-documented control mechanisms of protein synthesis is found through the action of small, single-stranded RNA, called micro RNAs (miRNAs or miRs). Put simply, miRNAs are negative regulators of the expression of a myriad proteins involved in many physiological and pathological processes. This mini review will briefly summarize what is currently known about the action of miRNAs over Cxs expression/function in different organs under some relevant physiological and pathological conditions